Functional Calsequestrin-1 Is Expressed in the Heart and Its Deficiency Is Causally Related to Malignant Hyperthermia-Like Arrhythmia. Issue 10 (7th September 2021) - Sun, Zhipeng; Wang, Luqi; Han, Lu; Wang, Yue; Zhou, Yuan; Li, Qiang; Wu, Yongquan; Talabieke, Shaletanati; Hou, Yunlong; Wu, Lulin; Liu, Ronghua; Fu, Zhiping; et al.
Abstract : Background: Calsequestrins (Casqs), comprising the Casq1 and Casq2 isoforms, buffer Ca 2+ and regulate its release in the sarcoplasmic reticulum of skeletal and cardiac muscle, respectively. Human inherited diseases associated with mutations in CASQ1 or CASQ2 include malignant hyperthermia/environmental heat stroke (MH/EHS) and catecholaminergic polymorphic ventricular tachycardia. However, patients with an MH/EHS event often experience arrhythmia for which the underlying mechanism remains unknown. Methods: Working hearts from conventional ( Casq1 -KO) and cardiac-specific ( Casq1 -CKO) Casq1 knockout mice were monitored in vivo and ex vivo by ECG and electric mapping, respectively. MH was induced by 2% isoflurane and treated intraperitoneally with dantrolene. Time-lapse imaging was used to monitor intracellular Ca 2+ activity in isolated mouse cardiomyocytes or neonatal rat ventricular myocytes with knockdown, overexpression, or truncation of the Casq1 gene. Conformational change in both Casqs was determined by cross-linking Western blot analysis. Results: Like patients with MH/EHS, Casq1 -KO and Casq1 -CKO mice had faster basal heart rate and ventricular tachycardia on exposure to 2% isoflurane, which could be relieved by dantrolene. Basal sinus tachycardia and ventricular ectopic electric triggering also occurred in Casq1 -KO hearts ex vivo. Accordingly, the ventricular cardiomyocytes from Casq1 -CKO mice displayed dantrolene-sensitive increased Ca 2+ waves and diastole premature Ca 2+ transients/oscillations on isoflurane. Neonatal rat ventricular myocytes with Casq1-knockdown had enhanced spontaneous Ca 2+ sparks/transients on isoflurane, whereas cells overexpressing Casq1 exhibited decreased Ca 2+ sparks/transients that were absent in cells with truncation of 9 amino acids at the C terminus of Casq1. Structural evaluation showed that most of the Casq1 protein was present as a polymer and physically interacted with ryanodine receptor-2 in the ventricular sarcoplasmic reticulum. The Casq1 isoform was also expressed in human myocardium. Mechanistically, exposure to 2% isoflurane or heating at 41 °C induced Casq1 oligomerization in mouse ventricular and skeletal muscle tissues, leading to a reduced Casq1/ryanodine receptor-2 interaction and increased ryanodine receptor-2 activity in the ventricle. Conclusions: Casq1 is expressed in the heart, where it regulates sarcoplasmic reticulum Ca 2+ release and heart rate. Casq1 deficiency independently causes MH/EHS-like ventricular arrhythmia by trigger-induced Casq1 oligomerization and a relief of its inhibitory effect on ryanodine receptor-2–mediated Ca 2+ release, thus revealing a new inherited arrhythmia and a novel mechanism for MH/EHS arrhythmogenesis. Abstract : Supplemental Digital Content is available in the text.